Dialectical Activity, Ritual, and Value: A Critique of Talbot Brewer. (27th December 2014) - Cordner, Christopher
Abstract: Talbot Brewer has argued that contemporary philosophy of action and ethics are hampered by a picture of human agency as essentially consisting in bringing about states of affairs – a "production‐oriented" conception of action. From classical sources, centrally including Aristotle, Brewer retrieves a different picture – of human activity as fundamentally "dialectical". Ritual activity, including a ritual dimension of many dialectical activities, affirms and deepens our human presence in and to the world, and to other human beings. I argue that this aspect of ritual activity cannot be adequately recognised in the terms of Brewer's dialectical account of human activity.